2019
DOI: 10.1002/cssc.201901668
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically Porous Co−N−C Cathode Catalyst Layers for Anion Exchange Membrane Fuel Cells

Abstract: As a new class of metal–nitrogen–carbon (M−N−C) material with 3 D microstructure, zeolitic imidazolate frameworks (ZIFs) are used to synthesize highly active electrocatalysts for the oxygen reduction reaction, as substitutes for commercial Pt/C in anion exchange membrane fuel cells. However, to form an effective catalyst layer (CL), the relationship between the microstructure of the ZIF‐derived catalyst and the fuel cell performance must be investigated. In this work, a hierarchically porous CL based on the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 43 publications
(46 reference statements)
0
22
0
Order By: Relevance
“…Reproduced with permission. [ 87 ] Copyright 2019, Wiley‐VCH. e) Schematic of an ionomer crosslinking immobilization strategy for CLs.…”
Section: Cathode Catalyst Layer and Orr Catalystmentioning
confidence: 99%
“…Reproduced with permission. [ 87 ] Copyright 2019, Wiley‐VCH. e) Schematic of an ionomer crosslinking immobilization strategy for CLs.…”
Section: Cathode Catalyst Layer and Orr Catalystmentioning
confidence: 99%
“…The catalyst showed high electrochemical surface area and electro-catalytic activity. Zhang et al [104] used carbon black and Co-zeolitic imidazolate frameworks (ZIF) as templates to control the morphology, which revealed that the smaller catalysts had a more homogeneous distribution of catalyst and ionomer and a higher power density in alkaline fuel cells. Along with high dispersion, Kotaro et al [105] determined that a monolayer of Pt on the carbon support allows for ultra-low Pt loading, high Pt utilization, and high tunability of the activity through the varying of the Pt shell.…”
Section: Morphologymentioning
confidence: 99%
“…Typically, the best performing mass loading of M-N-C catalysts in membrane electrode assemblies (MEAs) are generally range from 2 to 3 mg cm −2 . [49][50][51] However, the performance of our Co 1 /CNH 700 catalyst continues to with the loading amount of the catalyst, and the loading amount for its best performance is 6.0 mg cm −2 . It is believed that the 3D radial shape and porous nature of Co 1 /CNH 700 effectively facilitates the mass transfer of reactants and products, leading to the high utilization of active sites even in thick catalyst layers (Figure S19, Supporting Information).…”
Section: Evaluation Of the Aemfc Performance Of Co 1 /Cnh 700mentioning
confidence: 99%